Pharmacognostical standardisation of an epiphytic orchid, Luisia tenuifolia Blume. - Sakthi P. Sethuraman; Kumar P. Ramachandran (GarVal Editorial Ltda., 2022)
Context: Pharmacognostical standardization of crude drugs is essential before carrying out its scientific validation as it furnishes the identity and authenticity of the plant. Luisia tenuifolia Blume also known as 'slender leaved Luisia', has been found to be traditionally practised in treating cuts, boils, wounds and abscesses. Aims: To perform the pharmacognostical investigation of L. tenuifolia and thereby reporting the morpho-anatomical, histochemical and physico-chemical characteristics of the epiphyte. Methods: Anatomical characteristic features were observed from the transverse sections of the plant specimens while staining of the transverse sections by using suitable chemical reagents was performed for the histochemical analysis. Moreover, the powder microscopy, physicochemical parameters and fluorescence analysis were also carried out on the pulverised whole plants of L. tenuifolia. Results: The morphological and anatomical characteristics revealed in the study will remain as valuable diagnostic features in the botanical authentication of this orchid. The powder microscopical characters revealed the presence of epidermal fragments and paracytic stomata, fibres, vessel elements and sclereids. The histochemical profile of different parts of the epiphyte showed the localisation of tannins, starch, lipids, lignin, mucilage, protein, cutin and calcium oxalate crystals in the tissue system. The physico-chemical parameters and fluorescence observations determined the pharmacopoieal standards of the plant in powdered form. Conclusions: Thus, the study records the morpho-anatomical, histochemical and physicochemical standards of the whole plants of L. tenuifolia in order to achieve pharmacognostical standardization of this epiphytic orchid. Further, phytochemical standardization and pharmacological validation are under pipeline owing towards an effective phyto-pharmacological research.